ESTIMATION OF FORCE OF MORTALITY FROM THIRD DEGREE POLYNOMIAL OF lx - Ahbab Mohammad Fazle Rabbi; Shamal Chandra Karmaker (European Scientific Journal, ESJ, 2013)
Force of mortality is an effective tool for indicating mortality level for a population which is an instantaneous measure of probability of death in a particular instant given survival up to that time. As the force of mortality is a function of the life table number of survivors at a particular age x; in this study third degree polynomial model is fitted to estimate the force of mortality using life table of Matlab demographic surveillance area for both sexes respectively. With more than 99 percent stability of the fitted models, pattern of force of mortality illustrated that; after a certain age (around 55 years) the force of mortality increase sharply to the remaining age and after age 15 the force of mortality is lower for females compared to males for Matlab HDSS.